Soil characterisation used in ceramic industries and an analysis of its feasibility in ecological bricks - Queiroz, Abílio José Procópio; Morais, Crislene Rodrigues da Silva (Ambiente Construído, 2021)
n this study, we aimed to characterise soils of three sedimentary deposits used as raw material sources for ceramic industries located in the Brazilian semi-arid region. The samples were collected in deposits located in the cities of Barra de São Miguel, Juazeirinho and Santa Cecília. They were named, prepared and submitted to tests to determine the mineralogical, chemical, physical and thermal characteristics using the XRD, EDX, Casagrande, granulometric analysis, TG and DTA. The soils presented compositions containing quartz, alumina and hematite, predominantly with about 90% of the total, with well-defined peaks in the diffractograms confirming the statement, and averages of plasticity and granulometric distribution that fit them as silt-clay. When heated to 1000 °C, fire losses were 17%, 16% and 29% for samples from Barra de São Miguel, Juazeirinho and Santa Cecília, respectively, which is due to the dehydration and burning of organic matter. Thus, they have met the requirements of the Brazilian standards that deal to produce sealing (with sintering) and soil-cement bricks (by pressing). The studied deposits offer satisfactory raw material for the ceramics industry and can provide soil for soil-cement brick (ecological bricks) production.